2017
DOI: 10.3892/ol.2017.7090
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA‑34a overexpression inhibits cell migration and invasion via regulating SIRT1 in hepatocellular carcinoma

Abstract: Abstract. Hepatocellular carcinoma (HCC) remains one of the most common types of malignancy with high mortality and morbidity rates. Previous studies have suggested that microRNAs (miRs) serve pivotal functions in various types of tumor. The aim of the present study was to assess the association between miR-34a expression and HCC cell migration and invasion, and the potential underlying mechanisms. The miR-34a overexpression vector or scramble control was transfected into human Hep3B and Huh7 cell lines. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
(29 reference statements)
1
19
0
Order By: Relevance
“…Among these, mir-34a-5p was reported to be expressed at higher levels in wild type p53 than in the mutant GBM [ 22 ]. Furthermore, Notch-1 has already been validated as a miR-34a-5p target gene in several tumor histotypes [ 23 ] such as choriocarcinoma [ 24 ], breast cancer [ 25 ], and hepatocellular carcinoma [ 26 ]. We initially evaluated the levels of miR-34a-5p in both cell lines and in the normal brain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, mir-34a-5p was reported to be expressed at higher levels in wild type p53 than in the mutant GBM [ 22 ]. Furthermore, Notch-1 has already been validated as a miR-34a-5p target gene in several tumor histotypes [ 23 ] such as choriocarcinoma [ 24 ], breast cancer [ 25 ], and hepatocellular carcinoma [ 26 ]. We initially evaluated the levels of miR-34a-5p in both cell lines and in the normal brain.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, in the wild-type p53-expressing U87MG cell line, a relevant role is played by mir-34a-5p ( Figure 8 A). According to the tumor-suppressive role of this microRNA in different tumor histotypes [ 24 , 25 , 26 , 27 ], we found that its expression is strongly downregulated in GBM cell lines in comparison to the normal human brain ( Figure 2 ). Interestingly the Notch expression appears directly correlated to mir-34a-5p expression; in fact the normal human brain, where the expression of mir-34a-5p is upregulated, the Notch-1 expression appears strongly reduced ( Figure 2 B).…”
Section: Discussionmentioning
confidence: 99%
“…The tumorigenic influence of SIRT1 has been demonstrated in HCC in recent years, except for its influence on different biological reactions, such as inhibition of cell death and enhancement of proliferation, tumor stimulation, progression, and metastasis 23,24. It was verified that SIRT1 had an impact on tumorigenesis, metastasis, and clinical outcomes as well as resistance to chemotherapy in HCC, caused by deacetylation of tumor suppressor or oncogenic factors 25,26. Nevertheless, the role of SIRT1 in the regulation of M1-like macrophages and in HCC is unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Increasing researches have indicated that many miRNAs, including miR-34a [6], miR-211 [7], and miR-873 [8], are aberrantly expressed in HCC samples and exerted an effect in cell proliferation, apoptosis, and metastasis through regulating target mRNAs gene. Previous studies have shown that the miR-34a could affect the proliferation and apoptosis of hepatocellular carcinoma by regulating HDAC1 [9], c-Met [6], and SIRT1 [10]. At present, only Jiang G et al reported the expression level of SATB2 in hepatocellular carcinoma [7].…”
Section: Introductionmentioning
confidence: 99%